2018
DOI: 10.12659/msm.906648
|View full text |Cite
|
Sign up to set email alerts
|

Perineal Ultrasound Versus Magnetic Resonance Imaging (MRI) Detection for Evaluation of Pelvic Diaphragm in Resting State

Abstract: BackgroundThe aim of this study was to compare the consistency differences between ultrasound and MRI detection methods and the reliability between 2 independent observers.Material/MethodsUnder 2 kinds of states – the resting state and muscle contractions state – intra-class correlation coefficients (ICCs) were calculated and the consistency of 2 diagnostic methods was evaluated by 2 independent observers. We also assessed the interscorer reliability of the 2 observers.ResultsIn terms of the evaluation of biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…[20] It was also used to observe the morphology and function of the pelvic floor muscles and the changes in the pelvic floor structure of women with pelvic floor dysfunction. [21][22][23] Despite of these studies on the structure and function of pelvic floor, the investigation on correlating the pelvic floor parameters with FPFD upon treatment is sparse. Particularly, the effect of acupuncture treatment on the structure of pelvic floor has not been explored through ultrasonic imaging to the best knowledge of the authors.…”
Section: Discussionmentioning
confidence: 99%
“…[20] It was also used to observe the morphology and function of the pelvic floor muscles and the changes in the pelvic floor structure of women with pelvic floor dysfunction. [21][22][23] Despite of these studies on the structure and function of pelvic floor, the investigation on correlating the pelvic floor parameters with FPFD upon treatment is sparse. Particularly, the effect of acupuncture treatment on the structure of pelvic floor has not been explored through ultrasonic imaging to the best knowledge of the authors.…”
Section: Discussionmentioning
confidence: 99%
“…for the investigation of other pelvic floor pathologies, such as pelvic organ prolapse and levator ani defects, showing moderate‐to‐excellent correlation between the two modalities 25–28 . However no study to date has compared the correlation of these two methods in the evaluation of suburethral masses.…”
Section: Discussionmentioning
confidence: 99%
“…Figures 3 and 4 demonstrate the ability of 2D-TPUS and 3D-EVUS to produce images consistent with and comparable to MRI. Other studies have compared 3D-US to MRI for the investigation of other pelvic floor pathologies, such as pelvic organ prolapse and levator ani defects, showing moderate-to-excellent correlation between the two modalities [25][26][27][28] . However no study to date has compared the correlation of these two methods in the evaluation of suburethral masses.…”
Section: Ultrasoundmentioning
confidence: 99%
“…It should be stressed that by evaluating the pelvic diaphragm in patients with pelvic organ prolapse in the resting state, it was preliminarily confirmed that the consistency of ultrasound and MRI was only moderate. The comparison of these 2 diagnostic methods under the dynamic muscle contraction state needs to be further explored [ 46 ]. Our research, however, draws attention to the importance of the measurement of sEMG, and thus it fills a gap in the functional diagnosis of muscles in this area.…”
Section: Discussionmentioning
confidence: 99%